2019
DOI: 10.1159/000499499
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Expression but Not Activity of Collagenases MMP-1 and MMP-13 in Human Renal Carcinoma

Abstract: <b><i>Background:</i></b> Collagenases are enzymes starting collagen degradation. The role of collagenases in renal carcinoma development is not well understood. <b><i>Objective:</i></b> Evaluation of collagen content and collagenase expression and activity in human kidney cancers. <b><i>Methods:</i></b> Collagen content was measured by the hydroxyproline assay. The expression and the content of collagenases were evaluated by Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, ROC curves showed that MMP1 didn’t have a high predictive accuracy in LIHC, and thus the prognostic role of MMP1 in HCC remained of concern. Interestingly, we found that MMP1 expression was low in KICH, which is consistent with a prior study ( 21 ), but high expression of MMP1 was related to advanced clinical stage, and had poor prognosis. Therefore, we speculated that MMP1 may be involved in regulating a negative feedback regulatory mechanism in KICH.…”
Section: Discussionsupporting
confidence: 92%
“…However, ROC curves showed that MMP1 didn’t have a high predictive accuracy in LIHC, and thus the prognostic role of MMP1 in HCC remained of concern. Interestingly, we found that MMP1 expression was low in KICH, which is consistent with a prior study ( 21 ), but high expression of MMP1 was related to advanced clinical stage, and had poor prognosis. Therefore, we speculated that MMP1 may be involved in regulating a negative feedback regulatory mechanism in KICH.…”
Section: Discussionsupporting
confidence: 92%
“…and 42, respectively). Mechanisms of injury included traffic accidents (12), pedestrian hits by vehicles ( 5) and an oncoming subway (1), falls from height (6), hit by a fallen tree branch (1), committed (3) or attempted (4) suicide by jumping, and attempted suicide by throwing themselves in front of a train (4). Overall baseline characteristics are shown in Table 1.…”
Section: Plos Onementioning
confidence: 99%
“…MMP1 (collagenase-1) particularly cleaves interstitial collagens I, II, and III into characteristic 3/4 and 1/4 fragments [10,11]. Moreover, it degrades other extracellular components like, for example, proteoglycans or structural proteins, therefore enabling cell migration or the release of active molecules from ECM stores [12]. MMP1 is secreted by various cells, including fibroblasts, keratinocytes, endothelial cells, macrophages, and hepatocytes [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples for biochemical analysis were prepared according to the procedure described in our previous publications [23,24].…”
Section: Tissue Samplementioning
confidence: 99%
“…An activity assay was performed using the fluorimetric method, which was described previously [23,24,27,28]. Gelatinases were first isolated on a black 96-flat-bottom-well microplate (Greiner Bio-One, Rainbach im Mühlkreis, Austria) that was precoated with specific anti-human MMP-2 or MMP-9 antibodies (R&D Systems, the same as was used in the Western blot analysis).…”
Section: Gelatinase Activitymentioning
confidence: 99%